SIBS/MB WAY : striving for a cashless portuguese society - Gilman, Maria Madalena Salgado (2020)
Organizations act in very dynamic and rapidly changing environments, wherein they face multiple exogenous shocks that threaten their sustainability and competitive advantage. Therefore, it is of utmost importance that firms continuously adapt and change their strategies to find a fit with the changing environment in order to guarantee survival and remain competitive. Scholars have developed management literature on the importance of strategic change on firm’s alignment with unstable and dynamic environments. Moreover, the Dynamic Capability view, which illustrates how firms can achieve sustainable competitive advantage and cope with the changing ecosystems, has gained increased awareness over the years. In order to demonstrate a real-life example of Strategic Change and the dynamic capabilities' theory in action, this dissertation examines the case of SIBS's digital transformation. The teaching case focuses on SIBS' changing process, strategic reorientation and also examines how, by introducing MB WAY, SIBS coped with the payments industry's dynamism. This case clearly illustrates the firm’s imminent need for strategic change and the importance of the company’s use of dynamic capabilities to successfully adapt to the external environment and enact superior performance.